(untitled) - Trần, Ngọc Thiên Phương (Cần Thơ, 2010)
The main purpose of this to investigation into high school English language tearchers' belisfs and practice of group work & the extent to which these beliefs are reflected in their classroom practice.In addition, this study explores the contraints teachers face in applying group work in Vietnamese EFL context.
Keywords: Effective teaching,Tiếng Anh,Hiệu quả dạy học,English language; Dạy và học,Người học ngoại ngữ,Study and teaching,Foreign speakers